1997
DOI: 10.1111/j.1600-051x.1997.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined collagen membrane and hydroxyapatite/collagen chondroitin‐sulfate spacer placement in the treatment of 2‐wall intrabony defects in chronic adult and rapidly progressive periodontitis patients

Abstract: This study, confined to non-smokers, evaluated guided-tissue regeneration in deep 2-wall intrabony defects using a diphenylphosphorylazide-cross-linked bovine type I collagen membrane supported by a hydroxyapatite/collagen/chondroitin-sulfate spacer in 43 adult periodontitis (AP) and 14 rapidly progressive periodontitis (RPP) patients, no more than 1 defect being randomly selected for each patient. Before surgery and 6 months after surgery, plaque (PI) and sulcus bleeding (SBI) indices, probing pocket depths (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…The application of the SFA resulted in a mean postoperative REC increase of 0.4 mm, with eight of 10 patients exhibiting a reduced (≤1 mm) postoperative REC increase. This result is in contrast with previous studies 23,24,26 that reported substantially higher REC increases in deep intraosseous defects treated by a similar reconstructive technique. In this respect, the postoperative REC increase observed in our study was comparable to that reported in a study 27 in which intraosseous defects were accessed with a microsurgical approach for GTR.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The application of the SFA resulted in a mean postoperative REC increase of 0.4 mm, with eight of 10 patients exhibiting a reduced (≤1 mm) postoperative REC increase. This result is in contrast with previous studies 23,24,26 that reported substantially higher REC increases in deep intraosseous defects treated by a similar reconstructive technique. In this respect, the postoperative REC increase observed in our study was comparable to that reported in a study 27 in which intraosseous defects were accessed with a microsurgical approach for GTR.…”
Section: Discussioncontrasting
confidence: 99%
“…CAL gain ranged from 1 to 11 mm, with five of 10 defects showing a CAL gain ≥5 mm. Previous studies investigating the use of the graft biomaterial employed in the present study in association with a collagen‐based membrane 23 or a non‐resorbable expanded polytetrafluoroethylene membrane 24 in the treatment of intraosseous defects reported a mean CAL gain ranging from 3.0 to 4.2 mm. Differences in CAL gain between our study and previous studies using similar reconstructive technologies may be ascribed, in part, to differences in disease status (chronic/aggressive periodontitis) of the study population, 23 protocols for postoperative maintenance, follow‐up intervals, and flap design and soft tissue management.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, these reviews were limited to patients with the chronic periodontitis (CP) in subjects aged 21 years or older, and studies specifically treating AgP were excluded. Thus, there is only limited information regarding surgical therapy for AgP, and only few clinical trials comparing GTR and AF in AgP patients [11][12][13][14][15], mostly based on a limited number of subjects, comparing several defects within the same patient and utilising unclear randomisation procedures.…”
Section: Introductionmentioning
confidence: 98%
“…However, space protection around large defects is an important concern in GTR 5 . The combined use of graft materials and GTR in the treatment of periodontal intrabony defects resulted in positive outcomes and secured the space that is crucial for new tissue regeneration 6‐8 . In a study in which four filling materials in bone defects of similar dimensions were evaluated in the mandibles of miniature pigs, defects were covered with barrier membranes and allowed to heal for 4, 12, or 24 weeks.…”
mentioning
confidence: 99%